Identifikasi Identifikasi Jenis, Warna, dan Ukuran Mikroplastik pada Air dan Sedimen di Sungai Buntung, Kabupaten Sidoarjo, Jawa Timur - Amelia, Oktavia Eka; Suprayogi, Dedy; Nengse, Sulistiya (Teknik Lingkungan Universitas Islam Indonesia, 2025)
The river in Sidoarjo has been contaminated with microplastics. One of the rivers in Sidoarjo which has quite a lot of sources of pollution is the Buntung River, such as the presence of rubbish heaps and burning of rubbish around the river. This research aims to determine the type, color and size of microplastics, as well as differences in the abundance of microplastics in water and sediment in the Buntung River, Sidoarjo. This research is quantitative descriptive. The sampling locations were 6 locations. Sample preparation was carried out using a solution of 0.05 M Fe(II), 30% hydrogen peroxide (H2O2), and NaCl. Then the samples were identified using a stereo microscope and the EpView application, while for comparison of the average abundance of water and sediment using the Independent T-Test. The results showed that in the water samples the most dominant type was 39% fragments, 30% blue, 53% measuring 0.1 mm - 0.5 mm, and the average abundance was 3,725 particles/m3. Meanwhile, in the sediment samples, the most dominant type was fragments 46%, blue 28%, size 0.1 mm – 0.5 mm 70%, and an average abundance of 1,735 particles/kg. The results of statistical tests show that there are differences in the abundance of microplastics in the water and sediment in the Buntung River.